Shoot type influence on fruit set and fruit growth of tangor ortanique - da Cunha Barros, M.; Gravina, A. (Agrociencia Uruguay, 2006)
Shoot type influence in fruit set and fruit growth was studied in adult plants of tangor ‘Ortanique’ (Citrus sinensis L. Osb.x C.reticulata Bl.) grafted on Poncirus trifoliata L. Raf. under drip irrigation. The experiment was located in a commercial plot in Kiyú, San José (34º 60’ SL). Four hundred reproductive shoots were tagged (100 leafy single flowered, 100 leafy multiple flowered, 100 leafless multiple flowered and 100 leafless single flowered shoots) in a total number of 25 plants in a complete randomized design. These plants presented a mean flowering intensity of 20 flowers/100nodes. The abscission of reproductive structures lasted for a period of 90 days postbloom (DPB). Sixty percent of the total abscission was concentrated between 30 and 70 days. Fruitlet abscission in leafless shoots was higher than in leafy ones from 40 days after full bloom. In the latter group, multiple flowered shoots abscissed more than single ones. Final fruit set, considering all shoot types was high, reaching 15.3% of the total flowers. In the whole, leafy shoots presented a significantly higher fruit set percentage than leafless shoots. Considering each shoot type, leafy single flowered shoots reached 39.2%, followed by leafy multiple flowered (16.8%), leafless single flowered ( 9.9%) and leafless multiple flowered shoots (7.2%). Leafy single flowered shoots with five or more leaves presented higher fruit set than those with less than five leaves. Fruit growth in all cases adjusted to a logistic model, ending growth in 300 days. The highest growth rate was found between 70 and 90 days for all shoot types. Related to fruit size, fruits proceeding from leafy shoots reached higher values than those originated in leafless shoots, presenting a significantly higher peduncle diameter.